Biodistribution of biodegradable polymeric nano-carriers loaded with busulphan and designed for multimodal imaging. Issue 1 (December 2016) - Asem, Heba; Zhao, Ying; Ye, Fei; Barrefelt, Åsa; Abedi-Valugerdi, Manuchehr; El-Sayed, Ramy; El-Serafi, Ibrahim; Abu-Salah, Khalid; Hamm, Jörg; Muhammed, Mamoun; Hassan, Moustapha
Abstract Background Multifunctional nanocarriers for controlled drug delivery, imaging of disease development and follow-up of treatment efficacy are promising novel tools for disease diagnosis and treatment. In the current investigation, we present a multifunctional theranostic nanocarrier system for anticancer drug delivery and molecular imaging. Superparamagnetic iron oxide nanoparticles (SPIONs) as an MRI contrast agent and busulphan as a model for lipophilic antineoplastic drugs were encapsulated into poly (ethylene glycol)-co -poly (caprolactone) (PEG-PCL) micelles via the emulsion-evaporation method, and PEG-PCL was labelled with VivoTag 680XL fluorochrome for in vivo fluorescence imaging. Results Busulphan entrapment efficiency was 83% while the drug release showed a sustained pattern over 10 h. SPION loaded-PEG-PCL micelles showed contrast enhancement inT 2 *-weighted MRI with highr 2 * relaxivity. In vitro cellular uptake of PEG-PCL micelles labeled with fluorescein in J774A cells was found to be time-dependent. The maximum uptake was observed after 24 h of incubation. The biodistribution of PEG-PCL micelles functionalized with VivoTag 680XL was investigated in Balb/c mice over 48 h using in vivo fluorescence imaging. The results of real-time live imaging were then confirmed by ex vivo organ imaging and histological examination. Generally, PEG-PCL micelles were highly distributed into the lungs during the first 4 h post intravenous administration, then redistributed and accumulated in liver and spleen until 48 h post administration. No pathological impairment was found in the major organs studied. Conclusions Thus, with loaded contrast agent and conjugated fluorochrome, PEG-PCL micelles as biodegradable and biocompatible nanocarriers are efficient multimodal imaging agents, offering high drug loading capacity, and sustained drug release. These might offer high treatment efficacy and real-time tracking of the drug delivery system in vivo, which is crucial for designing of an efficient drug delivery system.